Protein time-temperature sensor for intelligent starch polymers - Santos, Carolina Toledo [UNESP]; Veiga-Santos, Pricila [UNESP]; Sestari, Patricia [UNESP]; Sorrini, Nathalia Carvalho [UNESP]; Roca, Roberto de Oliveira [UNESP] (Wiley-Blackwell, 2020)
As alternative to conventional electronic time-temperature sensors, a natural, nontoxic, biodegradable, and thermochromic protein-based sensor was investigated exploring myoglobin and myoglobin-nitrite proteins ability in changing color when exposed to temperature. Myoglobin extract and nitrite were added to the cassava starch thermoplastic sensor films and their thermochromic time-temperature ability were monitored through visual and instrumental color (L, a, b, Chroma, and hue angle) changes when exposed to 100 and 170 degrees C/60 min environments. Scanning electron microscopy analysis have indicated that myoglobin and/or myoglobin-nitrite extracts addition resulted in homogeneous materials. Samples were efficient in reporting temperature exposure during time, indicating their feasibility as additives for packaging or label time-temperature sensors. Practical applications The protein time-temperature sensor could increase the packed food security since manufacture, corroborating correct pasteurization or sterilization conditions; or at end consumer ' s houses, indicating that secure cooking temperatures were reached.